Pengaruh Kualitas Pelayanan Kesehatan Rawat Inap Terhadap Tingkat Kepuasaan Dan Loyalitas Pasien Di RSUD Sungai Dareh Kabupaten Dharmasraya - Mira Novita Irawan; Sefnedi Sefnedi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
Customer or patient has a high bargaining power in the transaction process one health care services. Based on the Ministry of Health (2004) Health Center is a technical implementation unit DHO / State responsible for organizing the development of health in a working area. These services may include quality of service is defined as the difference between expectations or customers' perception of what is acceptable to use a five-dimensional assessment scale consists of tangible, reliability, responsiveness, assurance and empathy. Further on patient satisfaction has been considered as an important contributor in the treatment and better health outcomes. As well as the loyalty of patients who have a very important influence on the development of a company or the health sector and other service providers. This type of research is quantitative non-probability where the total population used as a final sample size of 40 respondents conducted in May-June 2019 in RSUD Sungai Dareh Dharmasraya. The results showed that all three hypotheses can be accepted, because the results of data analysis on these three variables indicate the value of X greater than 1.96 and a significance value less than 0.05% with a positive value and the direction of the direct and indirect relationships. Thus it can be concluded that the higher quality of health care received by the patient's level of satisfaction and loyalty will also be high.